2018
DOI: 10.1159/000485851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravitreal Silicone Oil on Subfoveal Choroidal Thickness

Abstract: Purpose: To evaluate the effects of intravitreal silicone oil (SO) on subfoveal choroidal thickness (SFCT). Methods: A total of 60 patients with unilateral pseudophakic macula-off rhegmatogenous retinal detachment were treated with a three-port pars plana vitrectomy and a 5,700-cSt SO endo­tamponade and subsequent SO removal. SFCT was measured before and 3 months after SO removal. The main outcome measure was the difference between the SFCT of operated eyes and the fellow eyes. Results: Before SO removal, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
0
22
1
1
Order By: Relevance
“…Although silicone oil can provide a long duration of tamponade and enhances efficacy in difficult cases, applying the oil frequently leads to complications, such as keratopathy, glaucoma, or cataract [13][14][15][16]. Glaucoma is one of the most common complications following the use of silicone oil endotamponade, which occurs due to several pathophysiological mechanisms, including the pupillary block, inflammatory angle closure by synechiae, rubeosis of the iris, and migration of emulsified and non-emulsified silicone oil to the anterior chamber [14][15][16][17][18]. Infiltration and occlusion of the trabecular reticulum are believed to drive the pathophysiology of silicone-induced secondary open-angle glaucoma (OAG) [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Although silicone oil can provide a long duration of tamponade and enhances efficacy in difficult cases, applying the oil frequently leads to complications, such as keratopathy, glaucoma, or cataract [13][14][15][16]. Glaucoma is one of the most common complications following the use of silicone oil endotamponade, which occurs due to several pathophysiological mechanisms, including the pupillary block, inflammatory angle closure by synechiae, rubeosis of the iris, and migration of emulsified and non-emulsified silicone oil to the anterior chamber [14][15][16][17][18]. Infiltration and occlusion of the trabecular reticulum are believed to drive the pathophysiology of silicone-induced secondary open-angle glaucoma (OAG) [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective observational study, we observed a decrease in subfoveal choroidal thickness in the second month (8±2 weeks) following SO removal compared to the first month after the PPV and SO injection in patients who underwent PPV and SO injection due to RRD. Several studies have shown that choroidal thickness decreases after PPV (7)(8)(9). In a study regarding the changes in choroidal thickness in patients undergoing PPV and C3F8 injection due to RRD with macular involvement, it has shown that the subfoveal choroidal thickness has not changed (10).…”
Section: Discussionmentioning
confidence: 99%
“…SO has been used world widely in complicated vitreoretinopathy, meanwhile many toxic effects on intraocular structures were substantialized, including iris, ciliary body, trabecular meshwork, retina and optic nerve, etc 6 7 . Recently many authors have proved foveal thickness decreasing, EZ disruption, and even choroidal thickness decreasing after SO endotamponade [8][9][10] . The exact mechanism of SO toxicity is still unknown.…”
Section: Discussionmentioning
confidence: 99%